THE INFLUENCE OF TEACHER PERFORMANCE AND EDUCATIONAL SERVICES ON PARENTS' DECISIONS TO CHOOSE A SCHOOL MEDIATED BY PARENTS' SATISFACTION AT PENABUR SUMMARECON BEKASI JUNIOR HIGH SCHOOL - Rosari, Fransisca Andriana Titi; T. Widjaja, Bernard; Purnama, Eka Desy (MSJ : Majority Science Journal, 2025)
Education is the main foundation in forming a quality future generation. Teacher performance plays a central role in achieving the goal of quality education, but this performance is not only influenced by individual factors, but also by external factors such as school leadership and the quality of educational services. SMPK PENABUR Summarecon Bekasi, as the youngest school in the SMPK BPK PENABUR Jakarta environment, continues to strive to improve the quality of education and services, but to date the number of students has not reached the school's ideal capacity. Based on new student admission data for the past eleven years, the number of students still fluctuates and tends not to meet the school's capacity target. In addition, the results of the customer service index survey indicate that several indicators related to teacher performance and school services are still below the expected target. This indicates the need for an in-depth study of the factors that influence parents' decisions in choosing a school for their children, especially at SMPK PENABUR Summarecon Bekasi. This study aims to determine the influence of teacher performance and educational services on parents' decisions in choosing a school, with parental satisfaction as a mediating variable. Located at SMPK BPK PENABUR Jakarta and totaling 100 (One Hundred) Parents and all members of the population as well as samples so that this study is a census study. The results of this analysis indicate that all indicators used in this study are valid and reliable. This study uses a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) using SmartPLS 3.3 software. This study provides evidence of a positive and significant influence